Structural Connectivity of the Posterior Cingulum Is Related to Reexperiencing Symptoms in Posttraumatic Stress Disorder. (October 2018) - Weis, Carissa N.; Belleau, Emily L.; Pedersen, Walker S.; Miskovich, Tara A.; Larson, Christine L.
Posttraumatic stress disorder is a heterogeneous disorder with disturbances in hyperarousal or avoidance behaviors and intrusive or reexperiencing thoughts. The uncinate fasciculus and cingulum bundle are white matter pathways implicated in stress and trauma pathophysiology, yet their structural integrity related to posttraumatic stress disorder symptom domains is yet to be understood. Forty-four trauma-exposed young adults underwent structural and diffusion-weighted magnetic resonance imaging. Stress and trauma exposure indices and severity of posttraumatic stress disorder symptoms were collected and used to predict current integrity of the uncinate fasciculus and cingulum bundle. Severity of reexperiencing posttraumatic stress disorder symptoms was significantly related to increased fractional anisotropy ( r = .469 p < .001) and decreased mean diffusivity ( r = −.373, p = .013) of the right posterior cingulum bundle. No other findings emerged with respect to stress exposure or of hyperarousal ( p 's > 0.05) or avoidance ( p 's > 0.2) posttraumatic stress disorder symptoms. The posterior cingulum connects medial temporal lobe structures with visual areas in the occipital lobe and has been implicated in visual memory and self-referential thought. Increased structural connectivity along this pathway may therefore explain the emergence of reexperiencing posttraumatic stress disorder symptoms. This along with the lack of results with respect to stress exposure suggests that structural aberrations in white matter pathways are more strongly linked with the actual experience of stress-related psychological symptoms than just exposure to stress.